2016
DOI: 10.3855/jidc.8228
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of Candida ciferrii fungemia in an immunocompromised patient with Crohn’s and Mycobacterium bovis disease

Abstract: We present a case report of a fungal bloodstream infection due to an unusual pathogen. This is a 30 years-old female patient diagnosed with Crohn's disease and a disseminated Mycobacterium bovis infection subsequently complicated by fungemia due to the emergent yeast pathogen Candida ciferrii, who was unresponsive to fluconazole and made a full recovery after treatment with posaconazole. To our knowledge, this is the first report of Candida ciferrii isolation from blood in an adult associated to a central veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…ciferrii is an unusual species of Candida, which has been rarely reported as a cause of human infection mostly in patients with immunosuppression. [1][2][3]5,6 . Most of the reported C. ciferrii cases include malignant otitis externa and onychomycosis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ciferrii is an unusual species of Candida, which has been rarely reported as a cause of human infection mostly in patients with immunosuppression. [1][2][3]5,6 . Most of the reported C. ciferrii cases include malignant otitis externa and onychomycosis.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it was necessary to use posaconazole, a broadspectrum drug, to treat this patient. 11 De Gentile L et al, report six cases of toe-nail onyxis due to an unusual yeast species, Candida ciferrii. 12 Capoor et al, reported C. ciferrii in AML patient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the current available literatures, C. ciferrii is rarely isolated or an infrequent type of Candida species that is known to cause superficial pathogenicity [29][30][31]. Some papers have documented that C. ciferrii was able to cause blood stream infections [29][30][31], pulmonary infections [30,32], gangrenous infections [30], onchomycosis [33] and urinary tract infections [14]. Similarities among these infected patients include co-morbidities such as COPD, age, diabetes, malnutrition, malignancy, other chronic diseases, and immunosuppression [31,32].…”
Section: Resultsmentioning
confidence: 99%